Diagnosis and management of liver masses in pregnancy. (January 2016) - Milburn, James; Black, Mairead; Ahmed, Irfan; McLeman, Lindsay; Straiton, Jack; Danielian, Peter
Abstract : Key content: Liver masses are increasingly detected in pregnancy because of the widespread use of abdominal ultrasonography. Most lesions are benign and can be treated conservatively, although rarely these can lead to clinical symptoms and the potential for significant haemorrhage. Diagnosis of liver masses is made primarily through radiological assessment with blood tests and rarely by direct liver biopsy. Collaboration between the obstetric department and specialist liver multidisciplinary team is essential to ensure optimal management. Learning objectives: Review of liver masses in pregnancy. Overview of issues relevant in the prepregnancy and postpartum periods. Interventional management strategies for liver lesions. Ethical issues: Should the diagnosis of a liver mass lead to termination of pregnancy? When should ionising radiation be used to aid diagnosis of liver masses? Are doctors aware of the risk of bleeding from a benign liver mass?